Planting Media Effectiveness on Celery (Apium graveolens L.) Growth - Battong, Umar; Asman; Arsela, Primadiyanti; Ardaniah; Rahmisari, Hellina (Proceedings Series on Physical & Formal Sciences, 2025)
The study on the effectiveness of different planting media for growing celery (Apium graveolens L.) took place in Desa Tapis, Kabupaten Paser. Researchers set out to explore how various planting media could impact celery growth, using a randomized block design with three repetitions to ensure the results were reliable. The planting media tested included a control group (y1), a mixture of top soil and palm compost (y2), and a combination of top soil and husk charcoal (y3). The results were quite revealing. The different planting media had a significant impact on several growth factors, including the average height of the plants measured at 2, 4, and 6 weeks after planting (WAP). Other important metrics, such as the number of petioles and tillers at 6 WAP, as well as the fresh weight harvested at 6, 7, and 8 WAP, also showed notable differences. Additionally, root length measurements taken at 9 WAP highlighted the effectiveness of the planting media. Among the options tested, the combination of top soil and palm compost (y2) stood out as the best choice for promoting celery growth. This particular mix not only resulted in taller plants but also increased the number of petioles and tillers, along with greater fresh weight and root length. These findings suggest that using top soil with palm compost can significantly enhance celery growth, offering valuable insights for farmers and gardeners looking to improve their celery yields.